Interdecadal change in the relationship between El Niño in the decaying stage and the central China summer precipitation - Lin Chen; Gen Li (Climate Dynamics, 2022)

Interdecadal change in the influence of El Niño in the developing stage on the central China summer precipitation - Lin Chen; Gen Li; Shang-Min Long; Chujie Gao; Zhiyuan Zhang; Bo Lu (Climate Dynamics, 2022)

Electrocatalytic degradation of sulfamethylthiadiazole by GAC@Ni/Fe three-dimensional particle electrode - Siwen Li; Yingzi Lin; Suiyi Zhu; Gen Liu (Environmental Science and Pollution Research, 2022)

Biflavonoids from the twigs and leaves of Cephalotaxus oliveri Mast. and their α -glucosidase inhibitory activity - Min Song; Tong Xiao; Qiu-Shuang Wu; Hang Fai Kwok; Ging Chan; Li-Gen Lin; Xiao-Qi Zhang; Wen-Cai Ye; Sheng-Jiang He; Qing-Wen Zhang (Natural Product Research, 2022)

Optimization of aquaculture sustainability through ecological intensification in China - Shuang‐lin Dong; Yun‐wei Dong; Ling Cao; Johan Verreth; Yngvar Olsen; Wen‐jing Liu; Qi‐zhi Fang; Yan‐gen Zhou; Li Li; Jing‐yu Li; Yong‐tong Mu; Patrick Sorgeloos (Reviews in Aquaculture, 2022)
As the world's leading producer of farmed aquatic food products, China faces great uncertainty concerning the further sustainable development of its aquaculture industry due to high and increasing pressure from environmental and resource constraints. To realize truly sustainable development, it is imperative to establish an evaluation system that integrates social, economic, environmental and resource criteria, and optimizes aquaculture systems through a holistic approach. Here, we used analytical hierarchy processes combined with expert judgment and objective data to assess the sustainability of 10 major aquaculture production systems (APSs) in China. Based on the evaluation results, we propose the ecological intensification of aquaculture systems (ELIAS), rationally integrating anthropogenic inputs with aquaculture ecosystem services, to improve the sustainability of APSs. The holistic evaluation system and ELIAS are fundamental and critical for the future development of aquaculture in China and globally.

Cover Image, Volume 14, Issue 3 - Shuang‐lin Dong; Yun‐wei Dong; Ling Cao; Johan Verreth; Yngvar Olsen; Wen‐jing Liu; Qi‐zhi Fang; Yan‐gen Zhou; Li Li; Jing‐yu Li; Yong‐tong Mu; Patrick Sorgeloos (Reviews in Aquaculture, 2022)
The cover image is based on the Review Article Optimization of aquaculture sustainability through ecological intensification in China by Shuang‐lin Dong et al., https://doi.org/10.1111/raq.12648 image

Pinirhizobacter soli gen. nov., sp. nov., a novel low temperature resistant gammaproteobacterium in the family Rhodanobacteraceae isolated from rhizospheric soil of Larix gmelinii - Han Xue; Chun-gen Piao; Ying-hua Lin; Yong Li (Archives of Microbiology, 2022)